EFEK APRODISIAK LARUTAN BIJI PALA (Myristica fragrans Houtt.) TERHADAP PERILAKU MENCIT (Mus musculus) SEBAGAI SUMBER BELAJAR BIOLOGI - Santoso, Handoko; Zen, Suharno (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Aphrodisiacs are substances that function as stimulants to increase sexual behavior. Some plants that have been studied as aphrodisiacs. Based on this background, it is necessary to research The aphrodisiac effect of a solution of nutmeg (myristica fragrans houtt.) on the behavior of mice (Mus musculus). This type of research was a qualitative descriptive study consisting of five groups, each with three repetitions. There were 30 mice and each group had 6 mice. The parameters observed were calculating the total percentage of approach (introducing), riding (climbing), and coitus (coitus). The data in this study are descriptive qualitative where the results show an aphrodisiac effect. The primary data were then analyzed descriptively by the research objectives, while the quantitative data were processed by tabulation. Based on the results of the introducing activity study the K2 treatment (0.93 times) was greater than the other treatments, although the value was still small. The results of the research on climbing activity in the K2 treatment (0.55 times) were greater than the other treatments. The absence of aphrodisiac activity (coitus) in this study indicated a slow response to sexual activity, requiring a longer time to respond to female mice that were in estrus. Kata kunci: Aprodisiak, Biji pala, Sumber Belajar